2017
DOI: 10.1111/ajgw.12304
|View full text |Cite
|
Sign up to set email alerts
|

Fungal diversity during fermentation correlates with thiol concentration in wine

Abstract: Background and Aims: Agricultural products deriving from the same genotypic clone often have different physical and sensory properties that influence their overall quality and value. Microorganisms may play key roles throughout the production of many crops, affecting plant and fruit health and modifying plant materials to produce socially and economically important commodities. Following this idea, we investigated whether fungal diversity both prior to and during fermentation was correlated with the concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…This observation is consistent with the finding that an S. uvarum strain produces high levels of thiols compared to S. cerevisiae wine strains (Knight et al. 2018). The level of subtelomeric silencing may therefore play an important role in interspecies hybrids, such as S. pastorianus .…”
Section: Biosynthesis and Occurrence Of Fruity And Floral Aroma Composupporting
confidence: 93%
“…This observation is consistent with the finding that an S. uvarum strain produces high levels of thiols compared to S. cerevisiae wine strains (Knight et al. 2018). The level of subtelomeric silencing may therefore play an important role in interspecies hybrids, such as S. pastorianus .…”
Section: Biosynthesis and Occurrence Of Fruity And Floral Aroma Composupporting
confidence: 93%
“…For example, we found that several Saccharomyces species besides S. cerevisiae were mapped in our data, namely, Saccharomyces paradoxus and Saccharomyces pastorianus (Supplementary Table S4B). Since previous studies have reported that S. paradoxus is rarely found in wine fermentations (Sicard and Legras, 2011; Knight et al, 2018), and there is a close evolutionary relationship between S. cerevisiae and S. paradoxus (Borneman and Pretorius, 2015), it is possible that our mapping to S. paradoxus is an artifact driven by close sequence homology (Naumova et al, 2005). In order to overcome the database problems, we applied functional analysis and binning strategies to metagenomic data, to make the results less dependent on only a single database.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some studies have determined the contribution of particular non-Saccharomyces yeasts to wine composition, showing that some strains can be used to improve thiol concentration in wines. Furthermore, Knight et al (2018) suggest that the yeast diversity in spontaneous wine fermentations can be directly correlated with the final thiol concentrations in wine, highlighting the contribution of Saccharomyces uvarum strains on it.…”
Section: Varietal Thiols Of Winesmentioning
confidence: 93%